CONCEPTIONS AND PRACTICES OF ASSESSMENT: A CASE OF TEACHERS REPRESENTING IMPROVEMENT CONCEPTION - Azis, Astuti (TEFLIN Journal, 2015)
Despite numerous quantitative studies on teachers' conceptions and practices of assessment, little research exists regarding the unique assessment environment of Indonesia. This study uses both quantitative and qualitative data to examine how Indonesian junior high school teachers understand assessment and how their conceptions of assessment relate to their assessment practices. This mixed methods study adopted a participant selection model in which quantitative data was analysed to select participants for the qualitative phase. Participants of this study believed that the purpose of assessment was to improve teaching and learning and also to demonstrate the accountability of students and school. They tended to disagree with the view that assessment is irrelevant. Further analysis of the data revealed that teachers' conceptions of assessment were conflicted. They were keen to use assessment practices to improve their classroom teaching, but felt that the state-wide examination policy requirements constrained their efforts. This suggests that government, policy makers, and curriculum developers must work to build a strong synergy among themselves in order to share consistent goals with teachers. If cultural expectations of school assessment and government policy were aligned, Indonesian teachers may be better able to resolve conflict between their beliefs and assessment practices.